Grounding in English and Arabic news discourse - Khalil, Esam N. (Amsterdam ; Philadelphia : John Benjamins Pub. Co., 2000)
Grounding in English and Arabic News Discourse explores the discourse notion of grounding (viz. the foreground-background structure), and examines it in the various structures that occur in short news texts. A text-level approach to grounding and the differentiation between several core concepts relating to the various textual and non-textual structures, distinguish the book from other approaches in the field. A corpus-based analysis focuses on sentence-initial expressions and examines the grounding-signalling function of several markers in both English and Arabic. The analysis captures constra.
GROUNDING IN ENGLISH AND ARABIC NEWS DISCOURSE; Editorial page; Title page; LCC data; Table of contents; Preface; Chapter 1. Overview; Chapter 2. The Foreground-Background Structure as a Textual Phenomenon; Chapter 3. Schematic Manifestations of Text-Level Grounding; Chapter 4. Syntactic Manifestations of Text-Level Grounding; Chapter 5. Initial Position Marking of Grounding: The Case of Arabic News; Chapter 6. Sentence-Initial Markers; Chapter 7. Discussion; Appendix I: Glossary of Notions Used in the Study; Appendix II: Transliteration System; References; Index.
Enlargement of author's thesis (Ph. D)--University of Amsterdam, 1999.
Includes bibliographical references (pages 247-270) and index.
Print version record.
eBooks on EBSCOhost
Keywords: English language -- Grammar, Comparative -- Arabic; Arabic language -- Grammar, Comparative -- English; English language -- Discourse analysis; Arabic language -- Discourse analysis; Journalism -- Language; Anglais (Langue) -- Grammaire comparée -- Arabe; Arabe (Langue) -- Grammaire comparée -- Anglais; Anglais (Langue) -- Analyse du discours; Arabe (Langue) -- Analyse du discours; Journalisme -- Langage; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Arabic language -- Discourse analysis; Arabic language -- Grammar, Comparative -- English; English language -- Discourse analysis; English language -- Grammar, Comparative -- Arabic; Journalism -- Language; Nieuws; Informatiestructuren (linguïstiek); Tekstanalyse; Engels; Arabisch; Proefschriften (vorm)